1989
DOI: 10.1021/bi00429a060
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise mechanism of HIV reverse transcriptase: primer function of phosphorothioate oligodeoxynucleotide

Abstract: Primer recognition by purified HIV reverse transcriptase has been investigated. Earlier we found that the reaction pathway for DNA synthesis is ordered, with template-primer and free enzyme combining to form the first complex in the reaction sequence (Majumdar et al., 1988). We now find that d(C)28 is a linear competitive inhibitor of DNA synthesis against poly[r(A)].oligo[d(T)] as template.primer, indicating that d(C)28 and the template.primer combine with the same form of the enzyme in the reaction scheme, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(108 citation statements)
references
References 30 publications
11
97
0
Order By: Relevance
“…According to Majumdar et al (1988Majumdar et al ( , 1989) and our results (Andreola et al, 1993), HIV-1 RT is able to bind the primer before the template. We have shown that, in the absence of template, HIV-1 RT could correctly recognize the 3'9erminal nucleotide of primers bearing chemically reactive groups at the 5' end.…”
Section: Discussionsupporting
confidence: 68%
“…According to Majumdar et al (1988Majumdar et al ( , 1989) and our results (Andreola et al, 1993), HIV-1 RT is able to bind the primer before the template. We have shown that, in the absence of template, HIV-1 RT could correctly recognize the 3'9erminal nucleotide of primers bearing chemically reactive groups at the 5' end.…”
Section: Discussionsupporting
confidence: 68%
“…No targeted or untargeted liposome-encapsulated oligonucleotides inhibited syncytium formation (Fig. 1) when tested at a final concentration of 0.5 A.M, which is the concentration at which they efficiently inhibit HIV-1 replication (25 (19,20). The total incubation time post-infection was 7 days.…”
Section: Tm Of Oligonucleotide-rna Interactionsmentioning
confidence: 99%
“…Phosphorothioate oligonucleotides have been shown to inhibit the replication of HIV-1 in vitro by both sequence-non-specific (3,5,10,11) and specific processes (12)(13)(14)(15)(16), depending on the type of infection. In acutely infected cells, phosphorothioate oligonucleotides acted in a sequence-non-specific fashion probably by inhibition of viral binding and fusion (17,18) and/or viral reverse transcriptase (RT) (19,20). In chronically infected cells, however, only sequencespecific oligonucleotides are active, since after integration viruscell binding and reverse transcription are no longer relevant (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, addition bases of the longer S-ODNs offer more potential for non-specific contacts in the yield stronger intramolecular secondary structure, thereby reducing the likelihood of binding the telomerase target. It is known that the phosphorothioate oligonucleotides blocked the proliferation HIV-1 in infected cells in a nonsequence specific manner [43], probably the inhibition of reverse transcriptase [44,45] and/or the viral entry process [46,47]. Our previous study of the anti-HIV activities of antisense oligonucleotides indicated that a phosphorothioate oligonucleotide targeted to the HIV-1 gag gene was inhibitory, and the sense and the random sequence oligomers were also able to protect against HIV-1 induced CPE, but their anti-HIV-1 activities were weaker than that of the antisense phosphorothioate oligonucleotide (S-ODN-gag-AUG) [48].…”
Section: Resultsmentioning
confidence: 99%